Digital Forensic Tools And Techniques For Handling Digital Evidence - Khairunnisak, Khairunnisak; Widodo, Wahyu (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2023)
The development of information security issues in many sectors makes the skill of mastering digital forensic highly needed. Digital forensic is recently used not only to support legal proceedings but also to investigate many incidents like digital data manipulation, site hacking, and terrorism. In mastering the skill of digital forensic, investigators should have knowledge about the techniques and tools that will be used. This research is proposed to help investigators in enhancing and developing their skills in revealing the content of digital evidence with the result reviews from each area in the forensic field. The review in this study is based on the focus of the forensic area by giving detailed information about the functions, limitations, and advantages as well as the specific techniques of forensics that leads to the techniques of live forensic or static forensic. This research also discusses the non-technical things that affect the performance of forensic investigation including operational activities, investigated activities, and legal elements. Thus, the result of this research is expected to be beneficial for helping investigators in determining the appropriate tools to investigate the digital evidence. The further research can develop the activities of anti-forensics that can hinder the investigation processes.